La relación de la imprecisión y la redundancia léxica en la coherencia de los textos argumentativos de los estudiantes universitarios - Ramírez Rodríguez, Laritza (2020)
In this article, I bring together the results of my thesis research on the relationship between two lexical errors: lexical imprecision and redundancy in the coherence of freshmen’s college student argumentative texts. Coherence is defined as the construction of a unit of meaning without any contradiction between its parts, which contributes to the interpretation of the text from the lexical link with the content development of the text from minor spaces at the level of microstructures, relationship between sentences, as well as their relation with the text in general at the level of macrostructure. In the study, the main objective of the study was to analyze how lexical imprecision and redundancy generate semanticconsequences in these students’ textual coherence. The research had a quantitative approach, since the number of errors was first counted in order to statistically link them, through the SPSS program, with textual coherence. The study design is non-experimental and explanatory, since there is no manipulation of the variables. The results of the research can be summarized in that there is a positive relationship between the presence or absence of imprecision, impropriety, lexical redundancy and colloquialisms,and the consistency of the argumentative texts of the sample. That is, as the number of lexical errores increased, the texts became less coherent.